Intervention for Social Frailty Focusing on Physical Activity and Reducing Loneliness: A Randomized Controlled Trial - Gen A; Higuchi Y; Ueda T; Hashimoto T; Kozuki W; Murakami T; Ishigami M (Clinical Interventions in Aging)
Aki Gen, Yumi Higuchi, Tetsuya Ueda, Tomoko Hashimoto, Wataru Kozuki, Tatsunori Murakami, Mio Ishigami Graduate School of Rehabilitation Science, Osaka Metropolitan University, Habikino City, Osaka, JapanCorrespondence: Yumi Higuchi, Graduate School of Rehabilitation Science, Osaka Metropolitan University, 3-7-30 habikino, Habikino City, Osaka, 5830855, Japan, Tel +81 72 9502111, Fax +81 72 9502130, Email Higu_reha@omu.ac.jpPurpose: During the COVID-19 pandemic, older adults living in the community experienced reduced physical activity (PA) and heightened loneliness, particularly those with less frequent outings—a key factor of social frailty. Promoting PA may foster social participation, increase outings, and reduce loneliness. This study investigates the effects of a multi-component intervention on PA and loneliness in socially frail older adults.Materials and Methods: This single-blind, randomized controlled trial included 64 participants aged ≥ 60 years with social frailty and pre-frailty defined according to Makizako’s Social Frailty Index. Participants were randomly assigned to either the intervention (n = 34) or the control (n = 30) group. Over eight weeks, the intervention group attended a weekly 60-min multi-component program that included health education, exercise, and self-monitoring. A simple exercise booklet was distributed to the control group at baseline. For both groups, outcome measures were assessed at baseline and after eight weeks. PA was assessed using a triaxial accelerometer. Loneliness was measured using the three-item version of the UCLA Loneliness Scale. We used repeated-measures analysis of variance with group-by-time interactions to estimate the intervention effects following the intention-to-treat approach.Results: PA was not affected by the intervention. A significant group-by-time interaction was observed for loneliness, with a medium effect size (p < 0.05), indicating that loneliness was significantly reduced in the intervention group compared to the control group.Conclusion: The multi-component program aimed at promoting PA may contribute to the building of social relationships and reducing loneliness in older adults with social frailty and pre-frailty.Keywords: community-dwelling older adults, loneliness, multi-component program, physical activity, social frailty